2005
DOI: 10.1111/j.1440-1746.2004.03608.x
|View full text |Cite
|
Sign up to set email alerts
|

Human leukocyte antigen allele associations in type‐1 autoimmune hepatitis patients from western India

Abstract: The present study indicates that the HLA susceptibility to type 1 AIH in the different populations studied is complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 29 publications
0
7
1
Order By: Relevance
“…[24][25][26][27] Studies from western India have reported increase in frequency of DRB1*13, DRB1*03, DRB1*15, DRB1*14 alleles in patient group in comparison to the controls. 28,29 Contrary to this, our study has found that DRB1*08 and DRB1*04 to be associated with the disease. On subdividing the AIH type 1 patient group into pediatric and adult it was found that DRB1*04 was associated with the pediatric population and DRB1*08 was associated with the adult population.…”
Section: Discussioncontrasting
confidence: 51%
“…[24][25][26][27] Studies from western India have reported increase in frequency of DRB1*13, DRB1*03, DRB1*15, DRB1*14 alleles in patient group in comparison to the controls. 28,29 Contrary to this, our study has found that DRB1*08 and DRB1*04 to be associated with the disease. On subdividing the AIH type 1 patient group into pediatric and adult it was found that DRB1*04 was associated with the pediatric population and DRB1*08 was associated with the adult population.…”
Section: Discussioncontrasting
confidence: 51%
“…DRB1*0101 and DQB1*0301 are reported to be risk factors for the autoimmune condition rheumatoid arthritis,(41;42) while Cw*0102 is associated with both psoriasis(43) and autoimmune hepatitis. (44) Cw*0102, like HLA*B57, can act as ligand for KIR. (45) Lastly, DRB1*0301 is inversely associated with rheumatoid arthritis,(46) consistent with its inverse association with HCV clearance, though we note it also has positive associations with autoimmune hepatitis(47) and systemic lupus erythematosus.…”
Section: Discussionmentioning
confidence: 99%
“…HLA-DRB1*1501 (40%), HLA-DRB1*14 (30%), HLA-DRB1*0301 (20%) and HLA-DRB1*1301(15%) were increased in type I AIH patients from western India. 34 Recently, another study indicated that HLA-DRB1*04 (odds ratio: 3.292, p = 0.008) and DRB1*08 (odds ratio: 10.5, p = 0.027) were significantly associated with type I AIH in the north Indian population. In the same cohort, patients with type II AIH were found to be significantly associated with DRB1*14 (odds ratio: 3.5, p = 0.047).…”
Section: Epidemiology Natural History and Genetics Of Aihmentioning
confidence: 98%